Using Electrical Impedance Tomography in Flood Embankment System - Król, K.; Sikora, J.; Rymarczyk, T. (Acta Technica Jaurinensis, 2013)
A new nondestructive method of the flood embankment dampness was tested by the electrical impedance tomography. The basic information about the built measuring system, including prototype equipment is given. The setup was used to determine the dampness of the test flood blank on a specially built model. The boundary element method was used to solve the forward problem. The neural networks